Negative pole piece and preparation method thereof, sodium ion battery and electric equipment

By adding sodium bisodium oxalate to the active layer of the negative pole tablets of sodium ion batteries, the problem of rupture and reorganization of the SEI membrane during the circulation and discharge process is solved, and a more stable SEI membrane formation is achieved, and the cycle of the sodium ion battery is improved. Stability and electrochemical performance.

CN119361701APending Publication Date: 2025-01-24深圳为方能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411490544.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the cyclic charging and discharging process of sodium ion batteries, the volume expansion of the negative electrode leads to rupture and reorganization of the solid electrolyte interface (SEI) membrane, affecting the cycling and safety performance of the battery.

Method used

Sodium bisoxaloborate is added to the active layer material of the negative electrode sheet, and the inorganic products generated through the reduction of BOB-anions form a stable complex structure with the electrolyte reduction products, which promotes the dense and stable formation of the SEI film.

Benefits of technology

The first Kuron efficiency and cycle stability of sodium ion batteries have been improved, the cycle life of negative and batteries is prolonged, and the overall electrochemical properties of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361701A_ABST
    Figure CN119361701A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece and a preparation method thereof, a sodium ion battery and electric equipment, and relates to the field of sodium ion batteries. The negative pole piece comprises a current collector and an active layer located on one side of the current collector, and materials for forming the active layer comprise a dispersing agent, a conductive agent, a negative active substance, a binder and sodium bis (oxalato) borate. Sodium bis (oxalato) borate is added into the material for forming the active layer, BOB-anions are reduced to generate an inorganic product in the charge-discharge process, and the inorganic product and an electrolyte reduction product form a stable complexing structure, so that a compact and stable SEI film is favorably formed; the electrochemical performance such as the first coulombic efficiency and the cycling stability of the sodium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and in particular to a negative electrode plate and a preparation method thereof, a sodium ion battery and an electrical device. Background Art

[0002] At present, lithium-ion batteries have developed into a highly mature and widely used electrochemical energy storage technology system. However, with the continuous progress of production and life, the limited lithium resources and the performance limitations of lithium-ion batteries under wide temperature conditions have made it gradually difficult to meet the growing market demand. In this context, sodium-ion batteries (SIBs) have shown great potential as a powerful supplement to lithium-ion batteries due to their fast kinetic characteristics in low temperature areas and excellent safety performance under high temperature conditions, and have broad market application prospects. However, with the rapid development of the market, more stringent requirements are placed on the cycle life of sodium-ion batteries.

[0003] In sodium-ion batteries, negative electrode materials play a vital role in improving their cycle life. During the battery's cyclic charge and discharge process, the continuous insertion and extraction of sodium ions will cause the negative electrode volume to expand. In addition, during the first charge and discharge process, a solid electrolyte interface (SEI) film will form on the surface of the negative electrode. However, this SEI film is often unable to withstand the expansion of the negative electrode volume, resulting in rupture and reorganization. These ruptures may become active sites for sodium deposition, thereby accelerating the growth of sodium dendrites. This phenomenon not only seriously affects the cycle performance of sodium-ion batteries, but also poses a potential threat to their safety performance. Therefore, how to form a stable negative electrode / electrolyte interface during the charge and discharge process has become a key factor restricting the development of sodium-ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide a negative electrode plate and a preparation method thereof, a sodium ion battery and an electrical device to solve the above-mentioned problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A negative electrode sheet comprises a current collector and an active layer located on one side of the current collector, wherein materials forming the active layer comprise a dispersant, a conductive agent, a negative electrode active material, a binder and sodium bis(oxalatoborate).

[0007] According to an embodiment of the present application, based on the total mass of the dispersant, the conductive agent, the negative electrode active material, the binder and the sodium bis(oxalatoborate), the mass percentage of the dispersant is 0.1%-3%, the mass percentage of the conductive agent is 0.1%-4.5%, the mass percentage of the negative electrode active material is 90%-97.5%, the mass percentage of the binder is 0.1%-3%; the mass percentage of the sodium bis(oxalatoborate) is 0.1%-2%.

[0008] According to an embodiment of the present application, the dispersant includes at least one of sodium dialkylbenzene sulfonate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium lignin sulfonate, and sodium carboxymethylcellulose;

[0009] And / or, the conductive agent includes at least one of Ketjen black, carbon nanotubes, carbon fibers, reduced graphene oxide, Super P, carbon black, and acetylene black;

[0010] And / or, the negative electrode active material includes at least one of a carbon-based negative electrode material, an oxide negative electrode material, a sulfide negative electrode material, a selenide composite material, and an alloy-type negative electrode material, and the carbon-based negative electrode material includes hard carbon;

[0011] And / or, the binder includes at least one of polyvinyl alcohol, polyurethane, polyacrylic acid, styrene-butadiene rubber latex, guar gum, xanthan gum, sodium alginate, and polyvinylidene fluoride;

[0012] And / or, the current collector includes any one of copper foil, aluminum foil, carbon-coated aluminum foil, copper mesh, and aluminum mesh.

[0013] The present application also provides a method for preparing the negative electrode sheet as described above, comprising: mixing a dispersant, a conductive agent, a negative electrode active material, a binder, sodium bis(oxalatoborate) and water to obtain a negative electrode slurry; coating the negative electrode slurry on a current collector, drying, and rolling to obtain the negative electrode sheet.

[0014] According to an embodiment of the present application, the process of obtaining the negative electrode slurry includes: mixing a dispersant, a conductive agent and water to form a mixture A; mixing the mixture A with a negative electrode active material to form a mixture B; mixing the mixture B with a binder to form a negative electrode slurry; wherein sodium bis(oxalatoborate) is added in the step of forming the mixture A or forming the mixture B or forming the negative electrode slurry.

[0015] According to an embodiment of the present application, the viscosity of the negative electrode slurry is 500-6000 mPa·s.

[0016] According to an embodiment of the present application, the solid content of the negative electrode slurry is 25%-55%.

[0017] According to an embodiment of the present application, the drying temperature is 90-140° C., and the drying time is 2-10 minutes.

[0018] According to an embodiment of the present application, the coating method includes any one of transfer coating and extrusion coating.

[0019] The present application also provides a sodium ion battery, which includes the negative electrode sheet described above or the negative electrode sheet prepared by the preparation method of the negative electrode sheet described above.

[0020] The present application also provides an electrical device, which includes the sodium ion battery described above.

[0021] Compared with the prior art, the beneficial effects of this application include:

[0022] In the present invention, sodium bis(oxalatoborate) is added to the material forming the active layer, and during the charge and discharge process, BOB - Anion reduction will generate inorganic products, which form a stable complex structure with the electrolyte reduction product, help to form a dense and stable SEI film, and improve the electrochemical properties of sodium ion batteries such as the first coulombic efficiency and cycle stability.

[0023] The negative electrode plate prepared by the preparation method of the present application contains sodium bis(oxalatoborate) uniformly dispersed in the negative electrode plate, which can promote the synthesis of a stable SEI film during the charge and discharge process, and can effectively improve the first coulombic efficiency and cycle stability of the battery.

[0024] The sodium ion battery and electrical equipment of the present application both have excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0026] Figure 1 The figure is a comparison of the cycle performance of the batteries assembled with the negative electrode sheets of Examples 1-5 and Comparative Example 1. DETAILED DESCRIPTION

[0027] As used herein:

[0028] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0029] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0030] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0031] In these examples, parts and percentages are by mass unless otherwise indicated.

[0032] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0033] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0034] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0035] A negative electrode sheet comprises a current collector and an active layer located on one side of the current collector, wherein materials forming the active layer comprise a dispersant, a conductive agent, a negative electrode active material, a binder and sodium bis(oxalatoborate).

[0036] In the present application, sodium bis(oxalatoborate) is added to the material forming the active layer. Sodium bis(oxalatoborate) can promote the formation of a stable SEI film, which can effectively improve the cycle performance of the battery and extend the cycle life of the negative electrode and the battery.

[0037] According to an embodiment of the present application, based on the total mass of the dispersant, the conductive agent, the negative electrode active material, the binder and the sodium bis(oxalatoborate), the mass percentage of the dispersant is 0.1%-3%, the mass percentage of the conductive agent is 0.1%-4.5%, the mass percentage of the negative electrode active material is 90%-97.5%, the mass percentage of the binder is 0.1%-3%; the mass percentage of the sodium bis(oxalatoborate) is 0.1%-2%.

[0038] The mass percentage of sodium bis(oxalatoborate) in the present application is 0.1%-2%. When the content of sodium bis(oxalatoborate) is within this range, it can effectively promote the formation of a dense and stable SEI film, improve the electrochemical performance of the battery, and also enable the battery to have a higher energy density, which has a higher practical value. If the amount of sodium bis(oxalatoborate) added is too little, the promotion effect on the formation of the SEI film is limited, and the effect of improving the electrochemical performance of the battery is not significant. If the amount of sodium bis(oxalatoborate) added is too much, the content of the negative electrode active material is relatively small, which will lead to a decrease in the energy density of the battery, which is not conducive to actual production applications.

[0039] According to some embodiments of the present application, the mass percentage of the dispersant may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any value between 0.1% and 3%.

[0040] According to some embodiments of the present application, the mass percentage of the conductive agent may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or any value between 0.1% and 4.5%.

[0041] According to some embodiments of the present application, the mass percentage of the negative electrode active material can be 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5% or any value between 90% and 97.5%.

[0042] According to some embodiments of the present application, the mass percentage of the binder may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any value between 0.1% and 3%.

[0043] According to some embodiments of the present application, the mass percentage of sodium bis(oxalatoborate) may be 0.1%, 0.5%, 1%, 1.5%, 2% or any value between 0.1% and 2%.

[0044] According to an embodiment of the present application, the dispersant includes at least one of sodium dialkylbenzene sulfonate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium lignin sulfonate, and sodium carboxymethylcellulose;

[0045] And / or, the conductive agent includes at least one of Ketjen black, carbon nanotubes, carbon fibers, reduced graphene oxide, Super P, carbon black, and acetylene black;

[0046] And / or, the negative electrode active material includes at least one of a carbon-based negative electrode material, an oxide negative electrode material, a sulfide negative electrode material, a selenide composite material, and an alloy-type negative electrode material, and the carbon-based negative electrode material includes hard carbon;

[0047] And / or, the binder includes at least one of polyvinyl alcohol, polyurethane, polyacrylic acid, styrene-butadiene rubber latex, guar gum, xanthan gum, sodium alginate, and polyvinylidene fluoride;

[0048] And / or, the current collector includes any one of copper foil, aluminum foil, carbon-coated aluminum foil, copper mesh, and aluminum mesh.

[0049] The present application also provides a method for preparing a negative electrode sheet as described above, comprising: mixing a dispersant, a conductive agent, a negative electrode active material, a binder, sodium bis(oxalatoborate) and water to obtain a negative electrode slurry; coating the negative electrode slurry on a current collector, drying, and rolling to obtain a negative electrode sheet.

[0050] The method can be used to prepare a negative electrode sheet with excellent electrochemical performance. Moreover, the method of the present application has the advantages of simple process and low production cost, and is suitable for large-scale promotion and application.

[0051] According to an embodiment of the present application, the process of obtaining the negative electrode slurry includes: mixing a dispersant, a conductive agent and water to form a mixture A; mixing the mixture A with a negative electrode active material to form a mixture B; mixing the mixture B with a binder to form a negative electrode slurry; wherein sodium bis(oxalatoborate) is added in the step of forming the mixture A or forming the mixture B or forming the negative electrode slurry.

[0052] According to the embodiment of the present application, the viscosity of the negative electrode slurry is 500-6000mPa·s. When the viscosity of the negative electrode slurry is within the above range, it can ensure good leveling when the slurry is applied. Too low slurry viscosity will lead to problems such as difficulty in coating and drying, cracking of the coating, agglomeration of slurry particles, and poor consistency of surface density; if the viscosity of the slurry is too high, it will lead to poor fluidity, poor leveling performance and poor wetting effect on copper foil and aluminum foil.

[0053] According to some embodiments of the present application, the viscosity of the negative electrode slurry may be 500 mPa·s, 1000 mPa·s, 1500 mPa·s, 2000 mPa·s, 2500 mPa·s, 3000 mPa·s, 3500 mPa·s, 4000 mPa·s, 4500 mPa·s, 5000 mPa·s, 5500 mPa·s, 6000 mPa·s or any value between 500-6000 mPa·s.

[0054] According to an embodiment of the present application, the solid content of the negative electrode slurry is 25%-55%. The solid content in this range can ensure that the negative electrode slurry has a suitable viscosity.

[0055] According to some embodiments of the present application, the solid content of the negative electrode slurry may be 25%, 30%, 35%, 40%, 45%, 50%, 55% or any value between 25% and 55%.

[0056] According to an embodiment of the present application, the drying temperature is 90-140° C., and the drying time is 2-10 minutes.

[0057] According to some embodiments of the present application, the drying temperature may be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or any value between 90-140°C.

[0058] The drying time can be 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes or any value between 2 and 10 minutes.

[0059] According to an embodiment of the present application, the coating method includes any one of transfer coating and extrusion coating.

[0060] The present application also provides a sodium ion battery, which includes the negative electrode sheet described above or the negative electrode sheet prepared by the preparation method of the negative electrode sheet described above.

[0061] The present application also provides an electrical device, which includes the sodium ion battery described above.

[0062] The electrical equipment may be a means of transportation, an energy storage system, a portable electronic device, a wearable device, etc. In some embodiments, the electrical equipment may be an electric car, an electric bicycle, a drone, a home energy storage system, an industrial energy storage system, a mobile phone, a tablet computer, a laptop computer, a smart watch, smart glasses, etc.

[0063] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0064] 1. Preparation of negative electrode sheet

[0065] Example 1

[0066] Embodiment 1 provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0067] (1) 1% sodium carboxymethyl cellulose, 1.5% Super P and an appropriate amount of deionized water were stirred for one hour to uniformly mix to obtain a mixture A;

[0068] (2) adding 95.4% hard carbon to mixture A, stirring for three hours, and uniformly mixing to obtain mixture B;

[0069] (3) Add 2% styrene-butadiene rubber latex and 0.1% sodium bis(oxalatoborate) to mixture B, stir for half an hour, and evenly mix to obtain negative electrode slurry. The viscosity of the negative electrode slurry is tested to be 2137 mPa·s, and the solid content is 35%;

[0070] (4) The negative electrode slurry obtained in step (3) is transferred and coated onto aluminum foil, baked in an oven at 130° C. for 5 minutes, and then rolled to obtain a negative electrode sheet.

[0071] Example 2

[0072] Embodiment 2 provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0073] (1) 1% sodium carboxymethyl cellulose, 1.5% Super P and an appropriate amount of deionized water were stirred for one hour to uniformly mix to obtain a mixture A;

[0074] (2) adding 94.5% hard carbon to mixture A, stirring for three hours, and uniformly mixing to obtain mixture B;

[0075] (3) Add 2% styrene-butadiene rubber latex and 1% sodium bis(oxalatoborate) to mixture B, stir for half an hour, and evenly mix to obtain negative electrode slurry. The viscosity of the negative electrode slurry is tested to be 2085 mPa·s, and the solid content is 35%;

[0076] (4) The negative electrode slurry obtained in step (3) is transferred and coated onto aluminum foil, baked in an oven at 130° C. for 5 minutes, and then rolled to obtain a negative electrode sheet.

[0077] Example 3

[0078] Embodiment 3 provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0079] (1) 1% sodium carboxymethyl cellulose, 1.5% Super P and an appropriate amount of deionized water were stirred for one hour to uniformly mix to obtain a mixture A;

[0080] (2) adding 93.5% hard carbon to mixture A, stirring for three hours, and uniformly mixing to obtain mixture B;

[0081] (3) Add 2% styrene-butadiene rubber latex and 2% sodium bis(oxalatoborate) to mixture B, stir for half an hour, and evenly mix to obtain negative electrode slurry. The viscosity of the negative electrode slurry is tested to be 2168 mPa·s, and the solid content is 35%;

[0082] (4) The negative electrode slurry obtained in step (3) is transferred and coated onto aluminum foil, baked in an oven at 130° C. for 5 minutes, and then rolled to obtain a negative electrode sheet.

[0083] Example 4

[0084] Embodiment 4 provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0085] (1) 1% sodium carboxymethyl cellulose, 1.5% Super P and an appropriate amount of deionized water were stirred for one hour to uniformly mix to obtain a mixture A;

[0086] (2) adding 94.5% of hard carbon and 1% of sodium bis(oxalatoborate) to mixture A, stirring for three hours, and uniformly mixing to obtain mixture B;

[0087] (3) Add 2% styrene-butadiene rubber latex to mixture B, stir for half an hour, and evenly mix to obtain negative electrode slurry. The viscosity of the negative electrode slurry is tested to be 2130 mPa·s, and the solid content is 35%;

[0088] (4) The negative electrode slurry obtained in step (3) is transferred and coated onto aluminum foil, baked in an oven at 130° C. for 5 minutes, and then rolled to obtain a negative electrode sheet.

[0089] Example 5

[0090] Embodiment 5 provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0091] (1) 1% sodium carboxymethyl cellulose, 1.5% Super P, 1% sodium bis(oxalatoborate) and an appropriate amount of deionized water were stirred for one hour to uniformly mix to obtain a mixture A;

[0092] (2) adding 94.5% hard carbon to mixture A, stirring for three hours, and uniformly mixing to obtain mixture B;

[0093] (3) Add 2% styrene-butadiene rubber latex to mixture B, stir for half an hour, and evenly mix to obtain negative electrode slurry. The viscosity of the negative electrode slurry is tested to be 2145 mPa·s, and the solid content is 35%;

[0094] (4) The negative electrode slurry obtained in step (3) is transferred and coated onto aluminum foil, baked in an oven at 130° C. for 5 minutes, and then rolled to obtain a negative electrode sheet.

[0095] Comparative Example 1

[0096] Comparative Example 1 provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0097] (1) 1% sodium carboxymethyl cellulose, 1.5% Super P and an appropriate amount of deionized water were stirred for one hour to uniformly mix to obtain a mixture A;

[0098] (2) adding 95.5% hard carbon to mixture A, stirring for three hours, and uniformly mixing to obtain mixture B;

[0099] (3) Add 2% styrene-butadiene rubber latex to mixture B, stir for half an hour, and evenly mix to obtain negative electrode slurry. The viscosity of the negative electrode slurry is tested to be 2085 mPa·s, and the solid content is 35%;

[0100] (4) The negative electrode slurry obtained in step (3) is transferred and coated onto aluminum foil, baked in an oven at 130° C. for 5 minutes, and then rolled to obtain a negative electrode sheet.

[0101] 2. Performance test of negative electrode

[0102] The negative electrode obtained above was assembled into a 2025 button battery with a glass fiber separator, an electrolyte, a sodium sheet, and nickel foam. The assembled battery was placed for 12 hours and then subjected to a constant current charge and discharge test. The charge and discharge cycle performance of the battery was measured in an environment of 25±1°C, and the cycle performance test was performed within a charge and discharge voltage range of 0.01-3.00V.

[0103] Table 1 is a table showing the initial coulombic efficiency and energy density of the batteries assembled from the negative electrode sheets of Examples 1-5 and Comparative Example 1. Figure 1This is a comparison chart of the cycle performance of batteries assembled with the negative electrode sheets of Examples 1-5 and Comparative Example 1 at a current density of 0.5 A / g.

[0104] Table 1 The first coulombic efficiency and energy density of the negative electrode sheet battery of Examples 1-5 and Comparative Example 1

[0105] Group First coulombic efficiency Energy density (Wh / kg) Example 1 85.3% 196.5 Example 2 91.7% 213.5 Example 3 91.4% 205.1 Example 4 91.1% 211.2 Example 5 91.0% 210.8 Comparative Example 1 56.9% 164.2

[0106] As can be seen from Table 1, the first coulombic efficiency and energy density of Examples 1-5 are significantly better than those of Comparative Example 1.

[0107] Depend on Figure 1 It can be seen that in Comparative Example 1, sodium bis(oxalatoborate) is not added, and the cycle performance of Comparative Example 1 is significantly inferior to that of Examples 1-5. The capacity of Comparative Example 1 after 100 cycles is only 165.6 mAh / g, while the capacity of Example 2 after 100 cycles with the addition of 1% sodium bis(oxalatoborate) is 309.4 mAh / g, which is significantly higher than the capacity of Comparative Example 1. At the same time, Example 2 with the addition of 1% sodium bis(oxalatoborate) also has a higher first coulombic efficiency, which verifies that it can generate a denser SEI film during the first charge and discharge process and reduce side reactions in the battery. When Example 1 adds less (0.1%) sodium bis(oxalatoborate, the first coulombic efficiency of Example 1 is 85.3%, and the first coulombic efficiency of Example 1 is still better than that of Comparative Example 1. In Example 3, the addition amount of sodium bisoxalate borate is 2%, and its cycle performance effect is still better than that of Comparative Example 1, and is not much different from that of Example 2. However, as shown in Table 1, the energy density of Example 3 will drop to 205.1Wh / kg, indicating that with the further increase of the content of sodium bisoxalate borate, the energy density of the battery will decrease slightly, indicating that too high an addition amount of sodium bisoxalate borate is not conducive to the improvement of the battery energy density. The performance of Examples 4-5 is not much different from that of Example 2, indicating that adding sodium bisoxalate borate in different preparation processes of the negative electrode sheet has little effect on the results.

[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0109] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A negative electrode plate, characterized in that: The invention comprises a current collector and an active layer located on one side of the current collector, wherein the materials forming the active layer comprise a dispersant, a conductive agent, a negative electrode active material, a binder and sodium bis(oxalatoborate).

2. The negative electrode sheet according to claim 1, characterized in that: Based on the total mass of the dispersant, the conductive agent, the negative electrode active material, the binder and the sodium bis(oxalatoborate), the mass percentage of the dispersant is 0.1%-3%, the mass percentage of the conductive agent is 0.1%-4.5%, the mass percentage of the negative electrode active material is 90%-97.5%, the mass percentage of the binder is 0.1%-3%; the mass percentage of the sodium bis(oxalatoborate) is 0.1%-2%.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The dispersant includes at least one of sodium dialkylbenzene sulfonate, hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, sodium lignin sulfonate, and sodium carboxymethyl cellulose; And / or, the conductive agent includes at least one of Ketjen black, carbon nanotubes, carbon fibers, reduced graphene oxide, Super P, carbon black, and acetylene black; And / or, the negative electrode active material includes at least one of a carbon-based negative electrode material, an oxide negative electrode material, a sulfide negative electrode material, a selenide composite material, and an alloy-type negative electrode material, and the carbon-based negative electrode material includes hard carbon; And / or, the binder includes at least one of polyvinyl alcohol, polyurethane, polyacrylic acid, styrene-butadiene rubber latex, guar gum, xanthan gum, sodium alginate, and polyvinylidene fluoride; And / or, the current collector includes any one of copper foil, aluminum foil, carbon-coated aluminum foil, copper mesh, and aluminum mesh.

4. The method for preparing a negative electrode sheet according to any one of claims 1 to 3, characterized in that: include: A dispersant, a conductive agent, a negative electrode active material, a binder, sodium bis(oxalatoborate) and water are mixed to obtain a negative electrode slurry; the negative electrode slurry is coated on a current collector, dried, and rolled to obtain the negative electrode sheet.

5. The method for preparing a negative electrode sheet according to claim 4, characterized in that: The method of obtaining the negative electrode slurry comprises: mixing a dispersant, a conductive agent and water to form a mixture A; mixing the mixture A with a negative electrode active material to form a mixture B; and mixing the mixture B with a binder to form a negative electrode slurry; wherein sodium bis(oxalatoborate) is added in the step of forming the mixture A or forming the mixture B or forming the negative electrode slurry.

6. The method for preparing a negative electrode sheet according to claim 4, characterized in that: The viscosity of the negative electrode slurry is 500-6000 mPa·s; And / or, the solid content of the negative electrode slurry is 25%-55%.

7. The method for preparing a negative electrode sheet according to claim 4, characterized in that: The drying temperature is 90-140° C., and the drying time is 2-10 minutes.

8. The method for preparing a negative electrode sheet according to any one of claims 4 to 7, characterized in that: The coating method includes any one of transfer coating and extrusion coating.

9. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet according to any one of claims 1 to 3 or the negative electrode sheet prepared by the method for preparing the negative electrode sheet according to any one of claims 4 to 8.

10. An electrical device, characterized in that: The electrical equipment comprises the sodium ion battery according to claim 9.